Analyzing Students' Writing Error in Comparison Between Male and Female Students - Iman, Topan Rahmatul; Tuti, Winda Meirias (JIIP - Jurnal Ilmiah Ilmu Pendidikan, 2022)
This study aims to compare the errors made by the male and female students who learn English as their second language. This research is classified as qualitative study because the data in this study is in the form of words and the investigators are human beings. The participants of this study comprised 30 students at one of the universities in West Nusa Tenggara. They consisted of 15 men and 15 women. This study's data was gathered through a writing test. This was used to know the students’ errors in writing English. After collecting the data, the authors analyzed the data in four steps; identifying the errors, describing the errors, comparing male and female errors, and explaining the error. The results show that there are similarities and differences in the errors produced by the male and female students. The similarities are a missing verb, subject and verb agreement, problems with plural, double verbs, problems with prepositions, problems with the indefinite article, problems with pronoun, and problems with spelling. The differences are missing a missing a subject, missing a subject and a verb, Capital issues, Verb after modal auxiliary, problems with collocation, problem with a conjunction, and misorder of the word.